2010
DOI: 10.1007/s10059-010-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

δ-Catenin Affects the Localization and Stability of p120-Catenin by Competitively Interacting with E-Cadherin

Abstract: E-cadherin is a member of the cadherin family of Ca2+-dependent cell-cell adhesion molecules. p120-Catenin and δ-catenin are known to bind to similar juxtamembrane regions of E-cadherin, and p120-catenin is known to stabilize E-cadherin. However, the function of competition between p120-catenin and δ-catenin for the E-cadherin has not been fully explained. In this report, we show that cells overexpressing δ-catenin contain less p120-catenin than control cells at cell-cell interface and that this causes the re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…For example, we showed that polymorphisms in PAX6 and d-catenin (CTNND2) are associated with high-grade myopia 29,32,33,35 . PAX6 can directly control both CTNND2 and WNT7B expression 62,63 , and both molecular pathways can result in increased b-catenin nuclear translocation to activate Wnt signaling 64,65 . Independently, the CREAM consortium found that polymorphisms in RSPO1 and ZNRF3, which regulate Wnt signaling by controlling the turnover of Wnt receptors, were significantly associated with axial length 12,66 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, we showed that polymorphisms in PAX6 and d-catenin (CTNND2) are associated with high-grade myopia 29,32,33,35 . PAX6 can directly control both CTNND2 and WNT7B expression 62,63 , and both molecular pathways can result in increased b-catenin nuclear translocation to activate Wnt signaling 64,65 . Independently, the CREAM consortium found that polymorphisms in RSPO1 and ZNRF3, which regulate Wnt signaling by controlling the turnover of Wnt receptors, were significantly associated with axial length 12,66 .…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to compare the tumor growth rates and metastatic potentials of cells differentially expressing p120 and δ-catenin. Furthermore, our recent published data shows that p120 and δ-catenin compete with each other to interact with E-cadherin [53]. Therefore, future investigations are required to determine whether E-cadherin processing and/or endocytosis induced by p120 result in the same consequences as those induced by δ-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is a member of the cadherin family of Ca(2+)-dependent cell-cell adhesion molecules (26). It is a 120 kDa cell-cell adhesion molecule involved in the establishment of epithelial adherens junctions (27), and also is an important cell adhesion molecule that plays paramount roles in organ development and the maintenance of tissue integrity and normal epithelial cell phenotype (28).…”
Section: Discussionmentioning
confidence: 99%